Cauda equina syndrome associated with multiple lumbar arachnoid cysts in ankylosing spondylitis: improvement following surgical therapy. Issue 12 (December 1990) - Shaw, P J; Allcutt, D A; Bates, D; Crawford, P J
Abstract : A case of cauda equina syndrome with multiple lumbar arachnoid cysts complicating ankylosing spondylitis (AS) is described. The value of computerised tomography (CT) and magnetic resonance imaging (MRI) as a non-invasive means of establishing the diagnosis is emphasised. In contrast to previously reported cases the patient showed neurological improvement following surgical therapy. Surgery may be indicated in some patients, particularly when there is nerve root compression by the arachnoid cysts and when the patient is seen early before irreversible damage to the cauda equina has occurred.